T eoría, localización, y reflexión en la formación de profesores de lenguas extrajeras - Dantas-Whitney, Maria (Revista Perspectivas Educativas, 2016)
The field of teacher education is currently undergoing a paradigm shift. Traditionally the act of teaching has been viewed as the mastery of technical skills. T oday , with the current emphasis on sociocultural, reflective and critical approaches to learning, we have come to understand that teaching is a much more complex and situated process. We are starting to view teaching as a cognitive process, as opposed to a technical endeavor . This paper expands on this new view of teacher education by focusing on three themes: theory , localization, and collaborative reflection. Each of these themes is discussed through examples of activities and assignments used successfully in the preparation and training of second language teachers.